A case of Concha Bullosa and potentially related evidences. Concha bullosa discovered in the bones of a medieval skeleton from Brentonico, northeast Italy: a case report - Tonina, Enrica; Licata, Marta; Pangrazzi, Caterina; Maspero, Ugo; Romano, Luca; Larentis, Omar (Medicina Historica, 2018)
The pneumatization of the middle turbinate, called Concha Bullosa, is one of the most frequent variations of the ostiomeatal complex. Although in literature there is no clarity regarding the role of Concha Bullosa related to the onset or complication of other paranasal area disorders, it is not rare to find the latter in co-occurrence with Concha. The study we present, which was carried out on an archaeological sample, shows the simultaneous presence of Concha Bullosa and pneumocele and their possible correlations. Finally, this contribution acquired importance from the moment in which it was presented as a direct attestation of the evidence discovered in the ancient world.